On some deep-sea Stenheliinae from the Gulf of California and the west coast of the Baja California Peninsula (Mexico): Wellstenhelia euterpoides sp. nov., and Wellstenvalia wellsi gen. et sp. nov. (Copepoda: Harpacticoida: Miraciidae) - Gómez, Samuel; Cruz-Barraza, José Antonio (Zootaxa, 2021)
At present, only 11 species of harpacticoid copepods have been described from the deep sea of the Gulf of California and the west coast of the Baja California Peninsula. These efforts had until recently been focused exclusively on the families Ameiridae Boeck, Argestidae Por, and Rhizothrichidae Por. Preliminary analyses revealed also an important contribution of the subfamily Stenheliinae Brady (Miraciidae Dana) to the overall species richness and diversity of deep-sea benthic copepods from the west coast of the Baja California Peninsula, and the central and southern Gulf of California. One new species of the genus Wellstenhelia Karanovic & Kim, 2014, We. euterpoides sp. nov., and one new genus and species, Wellstenvalia wellsi gen. et sp. nov., are herein described from sediment samples taken at eight sampling stations in the west coast of the Baja California Peninsula and in the central and southern Gulf of California. Wellstenhelia euterpoides sp. nov. seems to be closely related to We. euterpe Karanovic & Kim, 2014 with which it shares the reduced armature complement of the baseoendopod of the female fifth leg. The so far monotypic genus Wellstenvalia gen. nov. was found to be closely related to Muohuysia Özdikmen, 2009 and Wellstenhelia. Some comments on the relationships between the new genus proposed here and other stenheliin genera and species are provided as a contribution towards the monophyly of the subfamily.